The Impact of 242Pu Speciation on the Bioaccumulation of Plutonium by Babylonia spirata from Jakarta Bay - Budiawan Budiawan; Mariska Winda Asrini; Wahyu Retno Prihatiningsih; Heny Suseno (Universitas Gadjah Mada, 2021)
The research of bioaccumulation Plutonium of Babylonia spirata from Jakarta Bay using 242Pu radiotracer has been conducted. The aquaria experiments were applied by two oxidation states of Pu speciation with three replications. The experiment was carried out by 2 steps, such as uptake and depuration. The bioavailability of 242Pu in the (III) and (IV) oxidation states from sea has been studied for Babylonia spirata. Biokinetics parameters, such as concentration factors (CFss), uptake rate constants (ku), elimination rate constants (ke), bioconcentration factors (BCF), and biological half-life (tb1/2), were investigated. The dissection is carried out to separate the parts of the gastropod's body so that the target organs for Plutonium contamination can be identified. Each part of the gastropod's body was prepared radiochemically and analyzed using an alpha spectrometer. The research shows that Pu4+ is potentially accumulated in greater value than Pu3+ by B. spirata, in which Pu is more rapidly distributed and retained longer in proboscis and gastrointestinal tract.